Infertility secondary to an infected hydrocele: A case report - Moayid Fallatah (Urology Case Reports, 2020)
Hydroceles are one of the most common causes of scrotal swelling affecting around 1% of the adult population. While hydroceles are usually asymptomatic, some hydroceles can lead to infertility. We will present a case of a 34-year-old man who was referred to our center as a case of primary infertility (sever oligospermia 1.1 million/ml) for 4 years and was found to have bilateral hydroceles (infected right hydrocele). At 18 months post bilateral hydrocelectomy, the patient's total sperm count improved to 43 Million/ml. Therefore, we highly recommend considering hydrocele as an etiology in any patient with idiopathic infertility. Keywords: Hydrocele, Infertility, Spermatogenesis